Exploring Youth Preferences for Collective Action: A Comparison of a Grassroots Initiative with a Union-Led One - Zientara, Piotr; Adamska-Mieruszewska, Joanna (Relations industrielles / Industrial Relations, 2024)
SummaryMany young individuals now prioritize involvement in collective action as a means to instigate societal change. Crucially, they have access to social media platforms, which help them connect with like-minded peers and coordinate efforts. Some of them may be thus more inclined to favour less conventional collective action over formal union membership. In this study, which draws on data from young British workers during the period from December 2022 to March 2023, we endeavoured to ascertain this cohort’s preferred approach to collective action. We distinguished between an informal grassroots initiative and one led by a labour union as a means to advance the rights of gig economy workers. To this end, we conducted a controlled online experiment. We focused exclusively on a specific age cohort within a particular timeframe, thus limiting our ability to determine generational differences in preferences for collective action and in attitudes toward unions. Nevertheless, the results do offer insights into the forms of collective action preferred by Generation Z. British youth were found to view the informal grassroots initiative more positively than the union-led one. However, they viewed the latter as potentially having greater influence on government policy. Furthermore, they were not significantly more willing to join one initiative than the other. Nonetheless, they were more inclined to recommend the grassroots initiative. This paper contributes to the body of research on the relationship between labour unions and young people. It also provides insight into how members of Generation Z think about various ways of participating in collective action.